Urgensi Pendidikan Al-Qur’an: Kajian Problematika Ketidakmampuan Membaca Al-Qur’an Dan Solusinya - Nurhanifah, Nurhanifah (Jumper: Journal of Educational Multidisciplinary Research, 2023)
Al-Qur'an is a way of life for Muslims everywhere. Therefore understanding and practicing the contents of the contents of the Qur'an is an obligation. To be able to understand the Qur'an, it means that you must be able to read it first. This makes it possible for every reader of the Qur'an to read according to predetermined rules or not carelessly when reading it. In fact, many children cannot read the Qur’an with the correct tajwid. We often pay attention to our surroundings, where there are still many children, teenagers and even adults who do not read the Qur'an properly. The purpose of this research is to find out what are the factors that affect the inability to read the Koran according to recitation and to find out the solution. This research uses the literature study research method, which is carried out by examining a number of journals or books related to the problem of the inability to read the Qur’an for children, adolescents and adults. The results of the discussion show that there are several solutions to overcome the inability to read the Qur’ran, namely: 1). Giving motivation to children, 2). Qur’an habituation education, 3). Appropriate Al-Qur'an teaching method, 4). Establishing the tahsin program of the Qur’an. Keywords: Problems; inability to read the Qur’an; solution